2020
DOI: 10.1111/ijpo.12729
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐based teasing in youth: Associations with metabolic and inflammatory markers

Abstract: Summary Background Research among adults suggests that weight stigma is associated with worsened cardiometabolic health. However, these relationships have not been examined among youth. Objective Assess associations between weight‐based teasing (WBT) and metabolic and inflammatory markers among two samples of youth: (1) a non‐treatment‐seeking sample and (2) a weight loss treatment‐seeking sample with obesity. Method Weight, height, adiposity, waist circumference and blood pressure were measured. Fasting blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The second objective was to assess whether perceived fat stigma predicted allostatic load among late adolescents and young adults in Indiana. Two previous studies have found positive associations between fat stigma and allostatic load in adults and older adults, but it remains to be seen whether this is the case among adolescents or young adults (though see Schvey et al’ (2021) findings on weight teasing and metabolic/inflammatory markers in youth). Adolescence is a time of self‐identity formation, which is a phase in life that has great potential to be negatively impacted by experiences with fat stigma via identity threat (Hand et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…The second objective was to assess whether perceived fat stigma predicted allostatic load among late adolescents and young adults in Indiana. Two previous studies have found positive associations between fat stigma and allostatic load in adults and older adults, but it remains to be seen whether this is the case among adolescents or young adults (though see Schvey et al’ (2021) findings on weight teasing and metabolic/inflammatory markers in youth). Adolescence is a time of self‐identity formation, which is a phase in life that has great potential to be negatively impacted by experiences with fat stigma via identity threat (Hand et al, 2017).…”
Section: Introductionmentioning
confidence: 93%